2018
DOI: 10.1088/2040-8986/aac5ba
|View full text |Cite
|
Sign up to set email alerts
|

Wavefronts, actions and caustics determined by the probability density of an Airy beam

Abstract: The main contribution of the present work is to use the probability density of an Airy beam to identify its maxima with the family of caustics associated with the wavefronts determined by the level curves of a one-parameter family of solutions to the Hamilton–Jacobi equation with a given potential. To this end, we give a classical mechanics characterization of a solution of the one-dimensional Schrödinger equation in free space determined by a complete integral of the Hamilton–Jacobi and Laplace equations in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
(77 reference statements)
1
17
0
Order By: Relevance
“…Additionally, we find that the physical phase for the Airy beam can be obtained from a geometric perspective since the physical phase of the beam and the geometrical wavefronts coincide over the caustic. We conjecture that these results are linked with the observations made by Espíndola-Ramos et al [4], González-Juárez and Silva-Ortigoza [33], for the Airy and Bessel beams; they found a family of caustics which characterize in qualitative and quantitative form all the maxima of the Probability Density Function. On the other hand, we find that if there are rays that cross the caustic in a non-tangent form, then a non-uniform interference pattern is generated near to the caustic, so that The zeros of the Madelung-Bohm potential (dashed red lines) and the caustic (blue curve).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Additionally, we find that the physical phase for the Airy beam can be obtained from a geometric perspective since the physical phase of the beam and the geometrical wavefronts coincide over the caustic. We conjecture that these results are linked with the observations made by Espíndola-Ramos et al [4], González-Juárez and Silva-Ortigoza [33], for the Airy and Bessel beams; they found a family of caustics which characterize in qualitative and quantitative form all the maxima of the Probability Density Function. On the other hand, we find that if there are rays that cross the caustic in a non-tangent form, then a non-uniform interference pattern is generated near to the caustic, so that The zeros of the Madelung-Bohm potential (dashed red lines) and the caustic (blue curve).…”
Section: Discussionsupporting
confidence: 85%
“…If S(x, P, t) is a solution to both the Hamilton-Jacobi equation and Laplace equation, then Φ(x, t) satisfies the Schrödinger equation for an arbitrary real function O(P ) [4,26]. Under these conditions, the rays are determined from the stationary points of S(x, P, t), that is to say…”
Section: The Geometrical Description Of a Wavefunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…On this line of research, it has been shown that from a geometrical optics point of view, each nondiffracting beam is characterized by a particular family of wavefronts and a caustic, which are invariant under a translation along the axis of propagation [15,16]. In the case of the Bessel, parabolic and Airy beams [17,18], the caustic provides a qualitative description of the maximum of the intensity, and although this is not true in general for the Mathieu beams [19], it is possible that this geometric analysis gives information for other known types of nondiffracting beams, such as hypergeometric beams [20], generalization of classical beams [21][22][23] or even beams with no analytical representation [24,25]. Therefore, we conclude that the geometrical optics approximation to an optical field is good enough if the caustic gives a qualitative description of the maximum of the intensity pattern.…”
Section: Introductionmentioning
confidence: 99%